Zimbabwe : 2001 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; Statement by the Executive Director for Zimbabwe and Statement by the Authorities of Zimbabwe. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that Zimbabwe's economic crisis has continued to deepen. The deterioration has mainly been the result of inappropriate macroeconomic policies and a general breakdown in the rule of law in the context of the government's fast-track land reform program launched in early 2000. This deterioration has undermined investor confidence, contributed to the rise in unemployment, destroyed capital, and eroded institutions important for economic development, thereby darkening the longer-term outlook. Real GDP is projected to contract by 8 1\2 percent in 2001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet